PRINSIP EVALUASI PEMBELAJARAN PAI - Zaniar Zaniar; Julhadi Julhadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The principles of evaluation in Islamic Religious Education (PAI) emphasize an assessment process that measures students’ cognitive, affective, and behavioral development comprehensively. Three core principles guide this process: objectivity, fairness, and Islamic values. Objectivity ensures that evaluation is conducted based on clear, measurable indicators and is free from personal bias, allowing results to accurately reflect students’ actual abilities. The principle of fairness requires teachers to provide equal and proportional opportunities for all students, avoiding any form of discrimination. Meanwhile, Islamic values guide the evaluation process to embody ethical qualities such as honesty, trustworthiness, compassion, and respect for human dignity. Integrating these three principles creates an evaluation system that is meaningful, humanistic, and aligned with the overarching goals of Islamic education.Keywords: Islamic education assessment, objectivity, fairness, Islamic values